Analisis Struktur Atap Baja Lengkung pada Lapangan Tenis: Analysis of curved roof on a Tennis Court - Dhony Priyo Suseno; Budiono Joko Nugroho; Achmad Kurniawan (Jurnal Suara Pengabdian 45, 2022)
Building security is a mandatory requirement that must be met by a building. Before being built, it is necessary to review academic studies and structural analysis in advance regarding the technical requirements of the building whether it meets the standards or not against existing regulations in Indonesia. Currently, the Brebes Regency Education, Youth and Sports Office has an outdoor tennis court that is not yet representative. So it is planned that the field will be upgraded to become a semi-indoor field, by adding a curved roof in the 2022 fiscal year. The purpose of this community service activity is to determine the safety of semi-indoor roof coverings from a structural point of view. The method of activities carried out to achieve the goal of Community Service (PPM) is the method of literature, field surveys, data processing and report preparation.